PENGARUH DEBT TO EQUITY RATIO, EARNING PER SHARE, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM SYARIAH PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2011-2015 - Cut Mia Rahmatul Ul Ya; Aliamin Aliamin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study aims to examine the influence of debt to equity ratio, earning per share, and firm size to syariah stock return. The samples of this research are the firms listed in JII (Jakarta Islamic Index) in 2011-2015. The Samples are collected using purposive sampling method and resulted 24 companies become the  final samples. Data by multiple linear regression analysis. The results of this research show that (1) debt to equity ratio, earning per share, and firm size simultaneously have influence for syariah stock return, (2) debt to equity ratio has negative influence and significant for syariah stock return, (3) earning per share has positive influence and significant for syariah stock return, and (4) firm size has positive influence and significant for syariah stock return.